Enciclopédia Luso-Brasileira de cultura (Verbo)
1.º vol.: A - Amor, 1870 p.; 2.º vol.: Amora - Australopiteco,1878 p.; 3.º vol.: Áustria - Brasil, 1912 p.; 4.º vol.: Brasília - Cerâmica, 1848 p.; 5.º vol.: Ceratite - Córrego, 1882 p.; 6.º vol.: Correia - Dumbi, 1846 p.; 7.º vol.: Dume - Europa, 1874 p.; 8.º vol.: Európio - Gabu, 1874 p.; 9.º vol.: Gacon - Hermenegildo, 1874 p.; 10.º vol.: Hermenêutica - Ironia, 1874 p.; 11.º vol.: Iroqueses - Libânio, 1874 p.; 12.º vol.: Líbano - Matrícula, 1870 p.; 13.º vol.: Matrimónio - Nerópolis, 1874 p.; 14.º vol.: Neruda - Pétain, 1908 p.; 15.º vol.: Pétala - Rede, 1910 p.; 16.º vol.: Redenção - Sezures, 1912 p.; 17.º vol.: Sfax - Travancore, 1910 p.; 18.º vol.: Travão - Zyl, 1830 p.; 19.º vol.: Suplemento A - G, 1495 p.; 20.º vol.: Suplemento H - Z, 1492 p.; 21.º vol.: Suplemento II A - Z, 1612 p.; 22.º vol.: Suplemento III A - Z, 952 p. + índice alfabético geral de artigos; 23.º vol.: Cronologia 1991 - 1994, 1794 + 5 p.;